PRINSIP‑PRINSIP HUKUM ADMINISTRASI NEGARA SEBAGAI MEKANISME PENCEGAHAN PENYALAHGUNAAN KEKUASAAN DI ERA REFORMASI BIROKRASI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article analyses the role of the principles of State Administrative Law (HAN)—legality, accountability, proportionality, transparency, and fairness—as a preventive mechanism against abuse of power in the era of bureaucratic reform in Indonesia after 1998. Through a normative juridical approach, the study identifies the relevance of HAN in supporting the digitisation of SPBE, the 2023 ASN Law, and the 2025-2045 RB Grand Design, in which these principles limit the discretion of officials through supervision by APIP, PTUN, Ombudsman, and KPK, which have reduced cases of maladministration. However, challenges such as feudal bureaucratic culture, overlapping regulations, systemic corruption (IPK 34/2023), and low digital literacy hinder optimal implementation. The conclusion emphasises HAN as a holistic instrument for preventing abuse of power, which requires harmonisation of norms, BerAKHLAK training, and institutional synergy to realise good governance towards Indonesia Emas 2045.